A signal self-compensated anti-pollution homocysteine ratio electrochemical aptamer sensor and a preparation method thereof

CN122962077APending Publication Date: 2026-10-23GANSU AGRI UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610897740.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-22
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

[0007]本发明旨在解决现有同型半胱氨酸电化学适配体传感器在复杂生物基质中抗污染能力不足、牛血清白蛋白封闭导致信号衰减、长期稳定性差等技术问题,提供一种具有信号自补偿抗污染能力、高选择性和长期稳定性的同型半胱氨酸比率电化学适配体传感器及其制备方法

Benefits of technology

(1)首次揭示了BSA封闭与比率信号的协同抗污染机制。现有技术中BSA仅作为常规封闭剂,本发明首次发现并主动利用“BSA封闭导致双信号同步衰减但比值恒定”的现象,将BSA从“常规封闭剂”提升为“抗污染协同元件”。这一发现解决了本领域长期存在的“抗污染与准确性不可兼得”的技术难题。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122962077A_ABST
    Figure CN122962077A_ABST
Patent Text Reader

Abstract

The application discloses a signal self-compensation anti-pollution homocysteine ratio electrochemical aptamer sensor and a preparation method thereof. The sensor comprises a glassy carbon electrode, an AuNPs / MXene composite film modified on the surface of the electrode, methylene blue internal standard molecules loaded in the composite film, homocysteine specific aptamers self-assembled through Au-S bonds and a bovine serum albumin blocking layer. The application first utilizes the synergistic anti-pollution mechanism of BSA blocking and ratio signal: BSA blocking causes the synchronous attenuation of Hcy response current and internal standard current, but the ratio of the two remains basically constant, realizing the multiple anti-pollution of 'MXene super-hydrophilic surface + BSA physical blocking' and 'ratio signal self-compensation'. The interference signal of the sensor to structural analogues is less than 5%, the ratio change rate is only 2.04% within 15 days, and the recovery rate is still as high as 94.2% in an extreme pollution environment (the electrode is immersed in BSA for 30 minutes for pretreatment). The ratio of the oxidation peak current of Hcy to the oxidation peak current of methylene blue is linear with the Hcy concentration in the range of 3.25 nM to 150 muM by using a differential pulse voltammetry method, and the detection limit is as low as 1.08 nM. The application has the advantages of high selectivity, good long-term stability, strong anti-pollution capacity, simple preparation process and the like, and can be used for accurate detection of homocysteine in serum samples.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of electrochemical biosensor technology, specifically relating to a ratiometric electrochemical aptamer sensor for homocysteine ​​detection, and more particularly to a homocysteine ​​ratiometric electrochemical aptamer sensor with signal self-compensation and anti-contamination capabilities, high selectivity and long-term stability, and its preparation method. Background Technology

[0002] Homocysteine ​​(Hcy) is a sulfur-containing amino acid and an important intermediate in methionine metabolism. Abnormally elevated Hcy levels in the blood (hyperhomocysteinemia) have been proven to be an independent risk factor for cardiovascular disease, Alzheimer's disease, diabetic complications, and various cancers. Therefore, accurate, rapid, and highly selective detection of Hcy is of great significance for clinical diagnosis, prognostic assessment, and preventive healthcare. Currently, Hcy detection methods mainly include chromatography, immunoassay, fluorescence analysis, and electrochemical analysis. Among these, electrochemical methods have received widespread attention in the field of Hcy detection due to their advantages such as fast response, ease of operation, low cost, and ease of miniaturization. However, the electrochemical detection of Hcy faces three major challenges: First, Hcy has a high oxidation overpotential and slow reaction kinetics on bare electrodes, resulting in insufficient sensitivity; second, Hcy has similar redox behavior to structurally similar sulfur-containing compounds (such as cysteine ​​Cys, glutathione GSH, and methionine Met), resulting in poor selectivity; and third, macromolecules such as proteins in complex biological matrices (such as serum) are prone to non-specific adsorption on the electrode surface, causing electrode contamination and signal drift.

[0003] Aptamers are a class of single-stranded oligonucleotides obtained through in vitro screening. They possess high affinity, high specificity, ease of synthesis, ease of modification, and good thermal stability, and are hailed as "chemical antibodies." McKeague et al. first screened out Hcy-specific DNA aptamers, and Saeed et al. immobilized them on the surface of a gold electrode to construct an Hcy electrochemical aptamer sensor, verifying the feasibility of this strategy. The introduction of aptamers effectively solved the selectivity problem of Hcy detection, but the improvement in sensitivity and anti-contamination ability remains limited. In recent years, nanomaterials have been widely used in the construction of electrochemical sensing interfaces. MXene, as a novel two-dimensional transition metal carbide / nitride (such as Ti3C2T), XMXene nanosheets, with their metallic conductivity, abundant surface functional groups (-O, -OH, -F), and good hydrophilicity, are ideal substrate materials for constructing electrochemical sensing platforms. However, strong van der Waals forces exist between the layers of MXene nanosheets, leading to irreversible recombination and a decrease in effective specific surface area and active sites. Gold nanoparticles (AuNPs), with their good biocompatibility, high conductivity, and easily functionalizable surface, can serve as ideal immobilization platforms for aptamers. Loading AuNPs onto the surface and interlayer of MXene can not only effectively suppress MXene recombination but also synergistically enhance the conductivity and electrocatalytic activity of the composite material. Previous studies have successfully used an in-situ reduction method to uniformly load AuNPs onto the MXene surface and constructed electrochemical sensors, demonstrating the application potential of this composite material in the sensing field.

[0004] To improve detection accuracy and anti-interference capabilities, ratiometric electrochemical sensors have emerged. These sensors simultaneously detect the target response signal and the internal reference signal, using their ratio for quantification. This effectively compensates for errors caused by environmental fluctuations, differences in electrode modification, and instrument drift. Chinese patent application CN117191907A discloses a ratiometric Hcy electrochemical aptamer sensor based on gold nanoparticles loaded on MXene / reduced graphene oxide hybrid aerogel (MGA-40), achieving a wide linear range (2.14 × 10⁻⁻⁴). 9 ~ 2.00×10⁻ 4The low detection limit (0.713 nM) provides a useful technical reference for the field. However, the above technical solutions still have the following shortcomings: (1) Complex material preparation process: The above solution uses MXene and graphene oxide (GO) to prepare hybrid aerogel MGA-40 through hydrothermal treatment and freeze drying, which involves multiple complicated processes, high energy consumption and long cycle, which is not conducive to large-scale production. (2) Inadequate AuNP loading method: The above solution uses physical mixing method to ultrasonically mix pre-synthesized AuNPs with MGA-40. The distribution uniformity of AuNPs and the interfacial binding strength are limited. Some AuNPs are easy to agglomerate, affecting electron transport efficiency and sensor reproducibility. (3) Insufficient understanding of BSA blocking effect: Although the above solution uses bovine serum albumin (BSA) as a blocking agent, it is only regarded as a routine "occupying unblocked sites" step. It does not realize that BSA blocking itself will cause different degrees of attenuation of Hcy response signal and internal standard signal, and it does not reveal the synergistic anti-contamination relationship between BSA blocking and ratio signal. (4) Lack of systematic validation of anti-contamination performance: The scheme does not provide comparative data on signal changes before and after BSA blocking, nor does it conduct a systematic evaluation of anti-contamination performance in real biological matrices (such as serum), and cannot prove whether the sensor loses quantitative accuracy while gaining anti-contamination ability. (5) Lack of long-term stability data: The scheme does not provide long-term stability data for more than a few days, which cannot meet the requirement of long-term reliable operation of the sensor in practical applications.

[0005] Furthermore, biofouling is a common challenge faced by electrochemical sensors in the detection of real biological samples. Complex biological matrices such as serum and urine contain a large number of amino acids, proteins, neurotransmitters, phenolic substances, and other macromolecules. These substances easily undergo non-specific adsorption, aggregation, or precipitation on the electrode surface, forming a dense, impermeable layer that hinders mass transfer of target molecules to the electrode surface, thus significantly reducing the sensor's sensitivity, selectivity, and long-term stability. This problem is particularly prominent for Hcy detection: Hcy detection typically requires complex matrices such as serum, where high concentrations of proteins (such as albumin and globulins) and other biomolecules can severely contaminate the electrode surface, leading to signal drift, increased background noise, and even sensor failure. In recent years, constructing antifouling electrochemical sensors has become a research hotspot. Researchers have developed various antifouling strategies, including the introduction of nanoporous materials (such as nanoporous gold and single-walled carbon nanotubes), polyethylene glycol (PEG) and its derivatives, zwitterionic polymers, and hydrophilic peptides. Among them, hydrophilic interfaces have attracted much attention because they can competitively repel biofouling through the hydration layer. Studies have shown that hydrophilic surfaces can tightly bind water molecules and replace adsorbed pollutants through dehydration mechanisms, thereby effectively resisting non-specific adsorption. However, existing antifouling materials still have the following shortcomings: (1) the preparation process of most materials is complex and costly; (2) some materials (such as PEG) are prone to oxidative degradation during long-term use; (3) antifouling materials that simultaneously possess excellent conductivity, good hydrophilicity, and simple preparation processes are still very scarce. In particular, no systematic reports have been found on antifouling electrochemical sensors for Hcy detection to date.

[0006] In summary, developing an Hcy ratio electrochemical aptamer sensor that is simple to prepare, possesses high selectivity, long-term stability, and anti-fouling capabilities is of significant clinical importance and urgently needed for application. This invention is proposed based on this technical problem. Summary of the Invention

[0007] This invention aims to address the technical problems of existing homocysteine ​​electrochemical aptamer sensors, such as insufficient resistance to contamination in complex biological matrices, signal attenuation due to bovine serum albumin blocking, and poor long-term stability. It provides a homocysteine ​​ratio electrochemical aptamer sensor with signal self-compensation and anti-contamination capabilities, high selectivity, and long-term stability, as well as its preparation method. This invention also relates to the application of this sensor in the preparation of homocysteine ​​detection kits.

[0008] To achieve the above objectives, this invention proposes a multi-layered anti-fouling strategy that combines "MXene superhydrophilic surface + BSA physical sealing" with "ratio signal self-compensation".

[0009] First, this invention provides a homocysteine ​​ratio electrochemical aptamer sensor with signal self-compensation and anti-fouling capabilities, comprising: Electrode substrate; An AuNPs / MXene composite film modified on the surface of an electrode substrate, wherein the AuNPs / MXene composite film is composed of gold nanoparticles uniformly loaded onto the surface and interlayer of MXene nanosheets by in-situ reduction method; Methylene blue (MB) internal standard molecules loaded in the AuNPs / MXene composite membrane; Thiol-modified homocysteine ​​(Hcy) specific aptamers that self-assemble on the surface of gold nanoparticles via Au-S bonds; Bovine serum albumin (BSA) sealing layer encapsulating sites on the electrode surface that are not occupied by aptamers; The sensor transmits a ratio signal I. Hcy / I MB To achieve quantitative detection of target substances.

[0010] Through extensive experiments, the inventors discovered that when the sensor surface is sealed using a BSA, the response current of the single-signal configuration (without MB) decreases by 14.3%. In the ratiometric dual-signal configuration of this invention, although the Hcy response current and MB internal standard current decrease by 13.5% and 17.7% respectively, the ratio I... Hcy / I MB The value changed from 3.35 to 3.52, a change of only 5.1%, remaining essentially constant (see Example 5). This phenomenon indicates that the ratiometric design can automatically compensate for the signal attenuation effect caused by BSA enclosure, enabling the sensor to gain anti-contamination capabilities without sacrificing quantitative accuracy.

[0011] Based on the above findings, this invention constructs a multi-layered anti-fouling system: The first layer is a physical anti-fouling barrier, synergistically composed of an MXene superhydrophilic surface and a BSA sealing layer. The abundant oxygen-containing functional groups (-O, -OH, -F) on the MXene surface endow it with excellent hydrophilicity. Water contact angle experiments confirm that the water contact angle of the AuNPs / MXene composite film is 30.24°, far lower than the 82.31° of the bare glassy carbon electrode. The superhydrophilic surface can competitively repel non-specific protein adsorption through the hydration layer. The BSA sealing layer further covers the remaining active sites on the electrode surface not occupied by aptamers, forming a dense physical barrier. The two work synergistically to reduce electrode contamination at its source. The second layer is a signal self-compensation anti-fouling barrier: a ratiometric dual-signal design (I... Hcy / I MBIt automatically compensates for signal attenuation caused by BSA closure, as well as signal drift due to environmental fluctuations and long-term use. When BSA closure causes synchronous attenuation of Hcy response current and internal standard MB current, the ratio between the two remains basically constant, achieving self-compensation and anti-contamination at the signal level.

[0012] In some embodiments of the present invention, the gold nanoparticles in the AuNPs / MXene composite film have a particle size of 12-20 nm; the MXene is a few-layer Ti3C2T. X It has an accordion-like layered structure.

[0013] In some embodiments of the present invention, the sensor has at least one of the following performance characteristics: interference signals to structural analogues cysteine, glutathione, and methionine are less than 5% of the Hcy response signal; during 15 days of continuous use, I Hcy / I MB The ratio change rate does not exceed 5%; after soaking in a phosphate buffer solution containing 1.0 mM BSA for 30 minutes, I Hcy / I MB The ratio change rate shall not exceed 5.5%; the spiked recovery rate of Hcy in diluted serum containing 1.0 mM BSA shall not be less than 90%.

[0014] In some embodiments of the present invention, the sensor has a linear detection range of 3.25 nM to 150 μM and a detection limit of 1.08 nM in a 0.2 M, pH 7.4 phosphate buffer solution.

[0015] Secondly, this invention provides a method for preparing a homocysteine ​​ratio electrochemical aptamer sensor with signal self-compensation and anti-pollution capabilities, comprising the following steps: (1) Preparation of MXene: LiF was dissolved in HCl solution, Ti3AlC2 powder was added, and the reaction was carried out at 34~37℃ for 22~25 hours. After washing until neutral, the mixture was ultrasonically exfoliated, centrifuged, and freeze-dried to obtain MXene nanosheets. (2) Preparation of AuNPs / MXene complex: The MXene obtained in step (1) was dispersed in HAuCl4 solution, heated to 70~90℃, and sodium citrate solution was quickly injected. The mixture was heated to boiling and refluxed for 10~20 minutes. After heating was stopped, the mixture was stirred for 10~20 minutes, cooled, centrifuged, washed, and freeze-dried to obtain AuNPs / MXene complex; wherein the molar ratio of HAuCl4 to sodium citrate was 1:3~1:5. (3) Preparation of AuNPs / MXene / MB dispersion: The AuNPs / MXene complex obtained in step (2) was redispersed in water to prepare a dispersion of 0.9~1.5 mg / mL. Methylene blue was added and the mixture was sonicated for 1~2 hours to obtain AuNPs / MXene / MB dispersion. (4) Preparation of ratiometric electrochemical aptamer sensor: The AuNPs / MXene / MB dispersion obtained in step (3) was drop-coated onto the surface of a glassy carbon electrode and dried to obtain AuNPs / MXene / MB / GCE; the thiolized homocysteine ​​aptamer was drop-coated onto the electrode surface and incubated at 4°C for 140-160 minutes to self-assemble via Au-S bonds; then it was placed in bovine serum albumin solution and incubated for 110-130 minutes to block unbound sites, thus obtaining the sensor; The BSA shutdown in step (4) causes the Hcy response current I to be blocked. Hcy and internal standard current I MB Synchronous decay, but the ratio I of the two Hcy / I MB By maintaining a basic constant, the sensor signal is endowed with self-compensating and anti-pollution capabilities.

[0016] In some embodiments of the present invention, the concentration of the aptamer in step four is 10 μM, and the concentration of the bovine serum albumin solution is 0.5~2.0 mM.

[0017] Finally, this invention provides the application of the above-described sensor or the sensor prepared by the above-described method in the preparation of a homocysteine ​​detection kit.

[0018] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention reveals for the first time the synergistic anti-contamination mechanism of BSA blocking and ratio signals. In the prior art, BSA is only used as a conventional blocking agent. This invention is the first to discover and actively utilize the phenomenon that "BSA blocking leads to synchronous attenuation of the two signals but the ratio remains constant", thus elevating BSA from a "conventional blocking agent" to an "anti-contamination synergistic element". This discovery solves the long-standing technical problem in the field that "anti-contamination and accuracy cannot be achieved simultaneously".

[0019] (2) Multiple physical anti-fouling barriers. This invention utilizes the superhydrophilic MXene surface (water contact angle 30.24°) and the BSA sealing layer to synergistically construct a physical anti-fouling barrier. The MXene hydrophilic surface repels non-specific protein adsorption through the hydration layer, and the BSA sealing layer covers the remaining active sites. The two work together to effectively reduce electrode contamination and provide a clean sensing interface for accurate detection of ratio signals.

[0020] (3) Excellent analytical performance. The sensor exhibits a linear detection range of 3.25 nM to 150 μM for Hcy in 0.2 M PBS (pH 7.4), with a detection limit as low as 1.08 nM. Electrochemical calculations show that the aptamer surface coverage density reaches 5.01 × 10⁻⁶. 12 molecules / cm 2 .

[0021] (4) Excellent selectivity. Based on the high affinity recognition of Hcy specific aptamers and combined with BSA blocking to reduce non-specific adsorption, the interference signals of the sensor of the present invention for structural analogues cysteine ​​(Cys), glutathione (GSH) and methionine (Met) are all less than 5% of the Hcy response signal (25 μM interference vs 10 μM Hcy).

[0022] (5) Excellent long-term stability (15 days). Continuous monitoring for 15 days showed that the Hcy response current I... Hcy The MB internal standard current I decreased by approximately 16.3%. MB It decreased by approximately 14.6% synchronously, but I Hcy / I MB The ratio change rate is only 2.04% (far below 5%). The ratio design of this invention effectively compensates for signal drift of up to 15 days, which is significantly better than the prior art.

[0023] (6) Verification of anti-contamination performance. After BSA blocking, the Hcy response current of the single-signal sensor decreased by 14.3%, while the current ratio of the ratio sensor of this invention only changed by 5.1%, proving that the ratio design can automatically compensate for the signal attenuation caused by BSA blocking. In the conventional diluted serum spike recovery experiment, the recovery rate of the single-signal sensor was 90.3% (RSD 4.28%), and that of the ratio sensor of this invention was 97.1% (RSD 3.54%), both of which can achieve effective detection. When 1.0 mMBSA coexists in the solution, the recovery rate of the single-signal sensor decreased significantly to 81.9% (RSD 6.53%), while the ratio sensor of this invention still maintained a high recovery rate of 96.4% (RSD 3.82%). Under even more severe contamination conditions (electrodes pre-soaked in 1.0 mM BSA solution for 30 minutes), the recovery rate of the single-signal sensor further plummeted to 73.2% (RSD 7.84%), while the ratiometric sensor of this invention still achieved a recovery rate of 94.2% (RSD 4.52%). These results fully demonstrate that the sensor of this invention exhibits significantly superior contamination resistance compared to the single-signal sensor in complex biological matrices.

[0024] (7) Structural advantages of in-situ synthesis. The present invention uses an in-situ reduction method to directly grow AuNPs on the surface and between layers of MXene. Compared with the physical mixing method in the prior art, in-situ synthesis achieves a more uniform distribution of AuNPs and a stronger interfacial bond, which significantly improves electron transport efficiency (charge transfer resistance is only 53.6 Ω).

[0025] (8) Simplified preparation process. The present invention uses pure MXene thin film modified electrode, without the need to introduce reduced graphene oxide (rGO) or construct complex aerogel structure, resulting in a shorter preparation process and lower cost. Attached Figure Description

[0027] Figure 1 Material morphology characterization diagram. Figure 1 A is a scanning electron microscope image of MXene; Figure 1 B is a transmission electron microscope image of MXene; Figure 1 C is a transmission electron microscope image of gold nanoparticles; Figure 1 D is a transmission electron microscopy image of the AuNPs / MXene complex.

[0028] Figure 2 Material structure characterization diagram. Figure 2 A represents the nitrogen adsorption-desorption curves for MXene and AuNPs / MXene; Figure 2 B is the corresponding DFT aperture distribution diagram; Figure 2 C represents the X-ray diffraction patterns of the MAX phase (curve a), MXene (curve b), and AuNPs / MXene (curve c); Figure 2 D represents the full X-ray photoelectron spectrum of MXene and AuNPs / MXene.

[0029] Figure 3 Characterization of the electrochemical performance of modified electrodes. Figure 3 A shows the cyclic voltammetry curves (scan rate: 50 mV / s) of AuNPs / GCE and AuNPs / MXene / GCE in 0.05 MH2SO4 solution. Figure 3 B represents the bare GCE, AuNPs / GCE, MXene / GCE, and AuNPs / MXene / GCE at 5.0 mM [Fe(CN)6]. 3⁻ / 4⁻ Electrochemical impedance spectroscopy in solution (containing 0.1 M KCl).

[0030] Figure 4 Comparison of antifouling performance of sensors with different configurations before and after BSA immersion (test conditions: 0.2 M PBS, pH 7.4, 100 μM Hcy). Figure 4A represents a comparison of the DPV response curves of Apt / GCE before and after BSA immersion; Figure 4 B represents a comparison of the DPV response curves of Apt / AuNPs / MXene / GCE (single signal) before and after BSA immersion; Figure 4 C represents a comparison of the DPV response curves of Apt / AuNPs / MXene / MB / GCE (ratio-type) before and after BSA immersion; Figure 4 D is a bar chart comparing the response currents of the three sensors before and after BSA immersion.

[0031] Figure 5 : Selectivity, reproducibility and long-term stability of the sensor. Figure 5 A is a bar chart showing the selectivity of the ratiometric sensor for 10 μM Hcy and 25 μM interfering substances (Cys, GSH, Met, etc.); Figure 5 B is a bar chart showing the reproducibility of the response of the five independently fabricated sensors to 100 μM Hcy. Figure 5 C is a superimposed graph of the sensor's DPV response curves to 20 μM Hcy over 1 to 15 days; Figure 5 D is a graph showing the changing trends of Hcy current, MB current, and their ratio with and without an internal reference signal.

[0032] Figure 6 : Sensor analytical performance. Figure 6 A shows the DPV response curves of the sensor to different concentrations of Hcy (3.25 nM~150 μM) (test conditions: 0.2 M PBS, pH 7.4, potential range -0.4~+0.8 V, amplitude 50 mV). Figure 6 B is I Hcy / I MB The graph shows the linear relationship between the ratio and Hcy concentration, with the inset showing the linear fit in the low concentration range (3.25 nM to 0.542 μM).

[0033] Figure 7 Comparison of water contact angles between bare glassy carbon electrode (GCE) and AuNPs / MXene composite membrane modified electrode. Detailed Implementation

[0034] The present invention will be further described in detail below with reference to specific embodiments, but the implementation of the present invention is not limited thereto. Experimental methods not specifying specific conditions in the embodiments are generally performed under conventional conditions or as recommended by the manufacturer. Reagents or instruments whose manufacturers are not specified are all commercially available conventional products.

[0035] Example 1: Preparation of MXene 1.98 g of LiF was dissolved in 20.0 mL of HCl solution (12.0 M) and stirred for 5 minutes. Then, 2.00 g of Ti3AlC2 powder was slowly added, and the mixture was reacted at 35 °C for 24 hours. The resulting mixture was washed with ultrapure water and centrifuged at 3500 rpm until the pH of the supernatant was close to 7.0. The precipitate was redispersed in ultrapure water and sonicated for 30 minutes. The supernatant was collected by centrifugation and freeze-dried to obtain MXene nanosheets.

[0036] Example 2: Preparation of AuNPs / MXene complex Weigh 10 mg of MXene into a round-bottom flask equipped with a condenser, add 50 mL of HAuCl4 solution (1.0 mM), and heat to 80 °C with continuous stirring. Then, rapidly inject 5 mL of sodium citrate solution (C6H5Na3O7, 38.8 mM), continue heating to boiling, and reflux for 15 minutes. Stop heating, maintain stirring for 10 minutes, and allow the reaction system to cool naturally to room temperature. Centrifuge the reaction mixture, wash the precipitate three times with distilled water, and freeze-dry to obtain AuNPs / MXene complex powder.

[0037] Materials and Electrochemical Characterization Figure 1 Images of different materials obtained using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Figure 1 As shown in Figure A, MXene exhibits a typical accordion-like layered structure, indicating that the Al layer was successfully etched. Figure 1 TEM images of B further confirm the two-dimensional nanosheet morphology of MXene. Figure 1 In C, gold nanoparticles (AuNPs) are uniformly dispersed spherical with a particle size of 16.2 ± 3.56 nm (n = 200). Figure 1 The D-distribution model shows that AuNPs are uniformly loaded on the surface and between layers of MXene, without agglomeration. These results demonstrate that the AuNPs / MXene composite material was successfully prepared by the in-situ reduction method of this invention.

[0038] Figure 2 A shows the nitrogen adsorption-desorption curves for MXene and AuNPs / MXene. The BET specific surface area of ​​AuNPs / MXene is 37.2 m². 2 g⁻ 1 Higher than 28.5 m of pure MXene. 2 g⁻ 1 This is attributed to the fact that the introduction of AuNPs inhibited the re-stacking of MXene nanosheets. Figure 2 The DFT pore size distribution diagram of B shows that the pore volume of AuNPs / MXene (0.103 m³) is... 3 g⁻ 1It is also greater than MXene (0.086m). 3 g⁻ 1 This indicates that the pore structure is optimized after loading AuNPs. Figure 2 C represents the X-ray diffraction pattern: Curve a is the MAX phase (Ti3AlC2), with its (002) peak located at 2θ = 9.29°; Curve b is MXene, with its (002) peak shifted to the left to 8.56°, and the (104) peak disappearing, indicating that the Al layer was successfully etched; Curve c is AuNPs / MXene, and in addition to the characteristic peak of MXene, face-centered cubic gold (111), (200), (220), and (311) crystal plane diffraction peaks (JCPDS No. 04-0784) appear at 2θ = 38.2°, 44.3°, 64.6°, and 77.5°, confirming the successful loading of AuNPs. Furthermore, the (002) peak of MXene further shifts to the left to 8.31°, indicating an increase in interlayer spacing. Figure 2 The XPS full spectrum of D shows that MXene contains C 1s, Ti 2p and O 1s peaks, and AuNPs / MXene additionally shows an Au 4f peak, further proving the successful introduction of AuNPs.

[0039] The electrochemical behavior of the modified electrode in 0.05 M H2SO4 was evaluated using cyclic voltammetry. Figure 3 In A, AuNPs / GCE (curve a) shows characteristic redox peaks of gold at +1.17 V and +0.836 V; AuNPs / MXene / GCE (curve b) has a significantly higher peak current, indicating that it has a larger electrochemical active area and higher electron transport efficiency, which is due to the high conductivity of MXene and the uniform dispersion of AuNPs. Figure 3 B represents the electrochemical impedance spectroscopy (measured at 5.0 mM [Fe(CN)6)). 3⁻ / 4⁻ +0.1 MKCl). The charge transfer resistance (Rct) of bare GCE is 310 Ω (curve a); AuNPs / GCE decreases to 228 Ω (curve b); MXene / GCE further decreases to 67.8 Ω (curve c); AuNPs / MXene / GCE has the lowest resistance at only 53.6 Ω (curve d). This indicates that AuNPs and MXene work synergistically to suppress MXene stacking, provide more electron transport channels, and significantly reduce interfacial impedance, proving that AuNPs / MXene is an ideal interfacial material for constructing high-performance electrochemical sensors.

[0040] Example 3: Preparation of AuNPs / MXene / MB dispersion The AuNPs / MXene complex powder was redispersed in water to prepare a dispersion of 1.2 mg / mL. 2.0 mL of this dispersion was taken, and 0.2 mg of methylene blue (MB) was added. The mixture was sonicated for 1 hour to obtain the AuNPs / MXene / MB composite dispersion.

[0041] Example 4: Fabrication of a ratiometric electrochemical aptamer sensor (1) Electrode pretreatment: The glassy carbon electrode (GCE, diameter 3 mm) was polished to a mirror finish with 0.05 μm Al2O3 and then ultrasonically cleaned with ethanol and ultrapure water in sequence.

[0042] (2) Modified electrode: 6.0 μL of the AuNPs / MXene / MB dispersion prepared in Example 3 was drop-coated onto the electrode surface and dried at room temperature for 30 minutes to obtain AuNPs / MXene / MB / GCE.

[0043] (3) Aptamer fixation: Take 6.0 μL of 10 μM thiolated Hcy aptamer (as shown in the sequence listing)<SEQ ID NO:1> The nucleotide sequence shown in the figure, with a thiol group -(CH2)6-SH modified at its 5′ end, is drop-coated onto the electrode surface and incubated at 4°C for 150 minutes. It then self-assembles through Au-S bonds to form Apt / AuNPs / MXene / MB / GCE.

[0044] sequence<SEQ ID NO:1> :5′-SH-(CH2)6-ACCA GCAC ATTC GATT ATAC CAGC TTAT TCAATTCA CAGC TATG TCCT ATAC CAGC TTAT TCAATT-3′; (4) BSA blocking: The above electrodes were incubated in 1.0 mM BSA solution for 120 minutes and rinsed with 0.2 M PBS (pH 7.4) to obtain the final sensor BSA / Apt / AuNPs / MXene / MB / GCE.

[0045] Example 5: Verification of BSA-induced signal self-compensation and anti-pollution measures Three aptamer sensor configurations were prepared: (a) bare GCE; (b) single-signal sensor (AuNPs / MXene / GCE, without MB); and (c) the ratiometric sensor of this invention (Apt / AuNPs / MXene / MB / GCE). The sensors were immersed in PBS solution (pH 7.4) containing 1.0 mM BSA for 30 minutes. Their response to 100 μM Hcy was tested using differential pulse voltammetry (DPV) before and after immersion to evaluate the anti-fouling ability of different sensors. Test parameters: potential range -0.4 ~ +0.8 V, amplitude 50 mV, pulse width 50 ms.

[0046] like Figure 4 As shown in Figure A, after immersion in BSA, the Hcy response current of the bare GCE decreased sharply, by 73.9%, indicating its extremely poor anti-fouling ability. Figure 4 As shown in Figure B, the Hcy response current of the single-signal sensor decreased after immersion in BSA, with a reduction of 14.3%. Although this is better than that of the bare electrode, there is still significant attenuation. Figure 4 As shown in Figure C, after immersion in BSA, although the Hcy response current (13.5%) and the MB internal standard current (17.7%) of the ratio sensor of this invention decrease simultaneously, their ratio I remains constant. Hcy / I MB The change was only 5.1%, essentially remaining constant. Figure 4 The bar chart for D visually compares the changes in response current of the three sensors before and after BSA immersion; detailed data are shown in Table 1. This result demonstrates that the ratiometric sensor of this invention effectively compensates for signal attenuation caused by BSA immersion through internal standard correction, achieving signal self-compensation and anti-contamination.

[0047] Table 1 Comparison of current response of sensors with different configurations before and after BSA immersion Example 6: Selective Experiment The sensor was tested for 10 μM Hcy and 25 μM potential interfering substances (Cys, Met, Arg, Trp, Tyr, AA, UA, GSH, Glu, H2O2, K⁺, Na⁺, Ca). 2+ Mg 2+ Fe 2+ The response to ( ). For example Figure 5 As shown in Figure A, the response signals of all interfering substances are less than 5% of the Hcy response signal, with Cys at 4.2%, GSH at 3.8%, and Met at 2.9%, demonstrating that the sensor of the present invention has excellent selectivity.

[0048] Example 7: Reproducibility Experiment Five sensors were independently fabricated under the same conditions, and their response to 100 μM Hcy was tested. Figure 5 As shown in B, I Hcy / I MB The relative standard deviation (RSD) of the ratio was 1.94% (n=5). This indicates that the fabrication process of the sensor of the present invention has good reproducibility and small batch-to-batch differences.

[0049] Example 8: Long-term stability test (15 days) The prepared sensor was stored at 4℃ and removed on days 1, 3, 5, 7, 9, 11, 13, and 15 to test its DPV response to 20 μM Hcy (the modified electrode surface was gently rinsed with 0.2 M pH 7.4 phosphate buffer solution after each test). The results are shown in Table 2 and... Figure 5 As shown in CD, within 15 days I Hcy A decrease of 16.3%, I MB The decrease of 14.6% and the change in ratio of only 2.04% (<5%) demonstrate that the ratio design effectively compensates for long-term signal drift.

[0050] Table 2 Results of 15-day long-term stability test Example 9: Performance Analysis Under optimal conditions (AuNPs / MXene concentration 1.2 mg / mL, aptamer 10 μM, fixation time 150 min, Hcy incubation 60 min, pH 7.4), the sensor's detection performance for Hcy is as follows: Figure 6 As shown. With increasing Hcy concentration, I Hcy Gradually increase, I MB Maintain stability. Hcy / I MB The ratio showed two linear relationships with Hcy concentration: in the low concentration range (3.25 nM~0.542 μM): I Hcy / I MB = 1.04 [Hcy](μM) + 0.0939, R 2 = 0.998; High concentration range (0.542 μM~150 μM): I Hcy / I MB = 0.0291 [Hcy] (μM) + 0.688, R 2 = 0.996. Therefore, the linear range of Hcy detection is 3.25 nM to 150 μM, and the detection limit is 1.08 nM.

[0051] Example 10: Characterization of water contact angle Water contact angle measurements were performed on bare glassy carbon electrodes and glassy carbon electrodes modified with AuNPs / MXene composite films using a contact angle meter. A 5 μL droplet of ultrapure water was placed on the electrode surface, allowed to stand for 5 seconds, and then an image of the droplet was captured. The contact angle was calculated. The results are as follows: Figure 7 As shown, the water contact angle of the bare glassy carbon electrode is 82.31±2.42°, exhibiting hydrophobic properties and easily leading to non-specific adsorption of biomolecules such as proteins. In contrast, the water contact angle of the electrode modified with the AuNPs / MXene composite film is significantly reduced to 30.24±1.64°, exhibiting superhydrophilic properties. The superhydrophilic surface can form a dense hydration layer, creating a physical barrier at the electrode-solution interface, effectively repelling contaminants such as proteins, thereby reducing non-specific adsorption at its source. This superhydrophilic surface, in synergy with the subsequent BSA sealing layer, constitutes the first physical anti-fouling barrier of this invention, providing a clean sensing interface for accurate detection of ratio signals.

[0052] Example 11: Serum Spike Recovery Experiment Serum from healthy volunteers (approved by the ethics committee) was centrifuged at 3000 rpm for 10 min to remove blood cells and at 12000 rpm for 15 min to remove proteins. The supernatant was diluted 10-fold with 0.1 M PBS (pH 7.4). Different concentrations of Hcy standards (1.00, 2.00, and 3.00 μM) were added to the diluted serum, and the ratiometric sensor of this invention was used for detection (n=3). The results are shown in Table 3. In 10-fold diluted human serum, the spiked recovery rate of the ratiometric sensor of this invention was 94.2%–104.6%, and the RSD was 2.96%–4.27%, indicating that the sensor has good accuracy and precision in real biological matrices and can meet the requirements of clinical sample detection.

[0053] Table 3 Results of routine serum spike recovery experiments Example 12: Anti-pollution spiked recovery experiment under extreme pollution conditions To evaluate the detection accuracy and anti-contamination ability of the sensor of the present invention under real serum matrix and extreme protein contamination conditions, the spiked recovery method was used for the experiment. Considering that human serum contains endogenous homocysteine ​​(Hcy), the background Hcy concentration in 10-fold diluted human serum was first determined, and then Hcy standard of known concentration was added to calculate the recovery rate. The following three detection environments were set up for the experiment: (1) No BSA (control): 10-fold diluted human serum + 3.00 μM Hcy; (2) 1.0 mM BSA coexisting in the solution: 10-fold diluted human serum + 1.0 mM BSA + 3.00 μM Hcy; (3) Electrode pretreatment by BSA immersion: After immersing the electrode in 1.0 mM BSA solution for 30 minutes, it was transferred to 10-fold diluted human serum without BSA + 3.00 μM Hcy for detection. The Hcy concentration in each group of solutions was detected using a single-signal sensor (Apt-AuNPs / MXene / GCE) and the ratiometric sensor of this invention (Apt-AuNPs / MXene / MB / GCE), respectively. Each group was measured three times (n=3), and the average value, spike recovery rate, and relative standard deviation (RSD) were calculated. The recovery rate was calculated using the formula: Recovery rate (%) = (Total measured value - Background value) / Spike amount × 100%. The experimental results are shown in Table 4.

[0054] Table 4 Comparison of spiked recovery experiments in different polluted environments (n=3) *Note: Adding BSA does not change the endogenous Hcy concentration; the background value is the same as the value measured by 10-fold dilution of human serum from the same batch.

[0055] †Note: After immersing the electrode in 1.0 mM BSA solution for 30 minutes, it was transferred to BSA-free spiked serum for detection.

[0056] As shown in Table 4, under conditions without BSA control, the spiked recovery rate of the single-signal sensor was 90.3% (RSD 4.28%), while that of the ratiometric sensor of this invention was 97.1% (RSD 3.54%). Both achieved effective detection, but the accuracy and precision of the sensor of this invention were superior, attributed to the ratiometric design effectively offsetting the matrix effect through internal standard correction. When 1.0 mM BSA was present in the solution, the recovery rate of the single-signal sensor decreased significantly to 81.9% (RSD 6.53%), indicating that high concentrations of protein underwent severe non-specific adsorption on the electrode surface, hindering mass transfer of target molecules to the electrode surface and resulting in insufficient anti-fouling ability; while the recovery rate of the ratiometric sensor of this invention remained as high as 96.4% (RSD 3.82%). Under extreme protein contamination conditions, pre-immersing the electrode in BSA solution for 30 minutes before detection further drastically reduced the recovery rate of the single-signal sensor to 73.2% (RSD 7.84%), while the ratiometric sensor of this invention still achieved a recovery rate of 94.2% (RSD 4.52%). The superior anticontamination performance of this invention is attributed to the synergistic effect of multiple anticontamination mechanisms: the first physical barrier is formed by the synergistic action of the MXene superhydrophilic surface (water contact angle 30.24°) and the BSA sealing layer; the former repels protein adsorption through the hydration layer, while the latter covers the remaining active sites, reducing electrode contamination at its source; the second signal self-compensation barrier is provided by the ratiometric dual-signal design, which maintains a stable ratio when residual contamination causes simultaneous decay of Hcy and MB currents, automatically compensating for signal loss. These results fully demonstrate that the sensor of this invention has significantly superior anticontamination capability and detection accuracy compared to single-signal sensors in complex biological matrices, meeting the needs of actual clinical testing.

[0057] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention. Those skilled in the art can make various improvements and modifications without departing from the spirit and principles of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.

Claims

1. A signal-self-compensating and anti-pollution homocysteine ​​ratio electrochemical aptamer sensor, characterized in that, include: Electrode substrate; An AuNPs / MXene composite film modified on the surface of an electrode substrate, wherein the AuNPs / MXene composite film is composed of gold nanoparticles AuNPs uniformly loaded onto the surface and interlayer of MXene nanosheets by in-situ reduction method; Methylene blue MB internal standard molecules loaded in the AuNPs / MXene composite membrane; Thiolized homocysteine ​​(Hcy) specific aptamers that self-assemble on the surface of gold nanoparticles via Au-S bonds; Bovine serum albumin (BSA) sealing layer encapsulated on electrode surface at sites not occupied by aptamers; The sensor transmits a ratio signal I. Hcy / I MB Achieve quantitative detection of target substances; The BSA sealing layer causes the Hcy response current I. Hcy and internal standard current I MB Synchronous decay, but the ratio I of the two Hcy / I MB The rate of change relative to before sealing does not exceed 5.5%, thus achieving signal self-compensation and anti-pollution.

2. The sensor according to claim 1, characterized in that, In the AuNPs / MXene composite film, the AuNPs have a particle size of 12~20 nm; the MXene is a few-layer Ti3C2T X It has an accordion-like layered structure; the water contact angle of the electrode surface modified by the composite film is 25°~35°, exhibiting superhydrophilic properties.

3. The sensor according to claim 1, characterized in that, The sensor has at least one of the following performance characteristics: High selectivity: The interference signals from structural analogues cysteine, glutathione, and methionine are less than 5% of the Hcy response signal; Long-term stability: During 15 days of continuous use, I Hcy / I MB The rate of change of the ratio shall not exceed 5%; Antifouling properties: After immersion in a phosphate buffer solution containing 1.0 mM BSA for 30 minutes, I Hcy / I MB The rate of change of the ratio shall not exceed 5.5%; Accuracy under extreme conditions: The recovery rate of Hcy spiked in diluted serum containing 1.0 mM BSA is not less than 90%.

4. The sensor according to claim 1, characterized in that, The sensor exhibits a linear detection range of 3.25 nM to 150 μM and a detection limit of 1.08 nM in a 0.2 M, pH 7.4 phosphate buffer solution.

5. A method for preparing a signal-self-compensating and anti-pollution homocysteine ​​ratio electrochemical aptamer sensor, comprising the following steps: (1) Preparation of MXene: LiF was dissolved in HCl solution, Ti3AlC2 powder was added, and the reaction was carried out at 34~37℃ for 22~25 hours. After washing until neutral, the mixture was ultrasonically exfoliated, centrifuged, and freeze-dried to obtain MXene nanosheets. (2) Preparation of AuNPs / MXene complex: The MXene obtained in step (1) was dispersed in HAuCl4 solution, heated to 70~90℃, and sodium citrate solution was quickly injected. The mixture was heated to boiling and refluxed for 10~20 minutes. After heating was stopped, the mixture was stirred for 10~20 minutes, cooled, centrifuged, washed, and freeze-dried to obtain AuNPs / MXene complex; wherein the molar ratio of HAuCl4 to sodium citrate was 1:3~1:

5. (3) Preparation of AuNPs / MXene / MB dispersion: The AuNPs / MXene complex obtained in step (2) was redispersed in water to prepare a dispersion of 0.9~1.5 mg / mL. Methylene blue was added and the mixture was sonicated for 1~2 hours to obtain AuNPs / MXene / MB dispersion. (4) Preparation of ratiometric electrochemical aptamer sensor: The AuNPs / MXene / MB dispersion obtained in step (3) was drop-coated onto the surface of a glassy carbon electrode and dried to obtain AuNPs / MXene / MB / GCE; the thiolized homocysteine ​​aptamer was drop-coated onto the electrode surface and incubated at 4°C for 140-160 minutes to self-assemble via Au-S bonds; then it was placed in bovine serum albumin solution and incubated for 110-130 minutes to block unbound sites, thus obtaining the sensor; The characteristic feature is that the BSA blocking in step (4) causes the Hcy response current I Hcy and internal standard current I MB Synchronous decay, but the ratio I of the two Hcy / I MB By maintaining a basic constant, the sensor signal is endowed with self-compensating and anti-pollution capabilities.

6. The preparation method according to claim 5, characterized in that, In step (4), the concentration of the aptamer is 10 μM and the concentration of the bovine serum albumin solution is 0.5~2.0 mM.

7. The use of the sensor according to any one of claims 1-4 in the preparation of a homocysteine ​​detection kit.

Citation Information

Patent Citations

  • Preparation and application of ratio type electrochemical aptamer sensor for detecting homocysteine

    CN117191907A